Variants in the 3′ End of SLC6A3 in Northwest Han Population with Parkinson’s - Peiye Chang; Yongwang Fu; Ping Zhao; Chunmei Wang; Mingfang Jiang; Rui Li; Yulin He (Parkinson's Disease)
Parkinson’s disease (PD) is one of the most common neurodegenerative disorders in neurology. It is possible that multifactorial and genetic factors are related to its pathogenesis. Recently, there have been reports of SLC6A3 genetic variants leading to PD. However, the role of 3′ end of SLC6A3 in PD is less studied in different ethnic groups. To explore the roles of 3′ end of SLC6A3 in PD development, 17 SNP sites in 3′ end of SLC6A3 were analyzed in 360 PD patients and 392 normal controls of Han population residing in northwest of China. The significant difference of gene type and allele frequencies between the PD and control groups was detected only in rs40184 (P = 0.013 and 0.004, respectively; odds ratio 2.529, 95% confidence interval 1.325–4.827). The genotype and allele frequencies of the other 16 SNP sites were not found to be different between the PD group and the control group. rs2550936, rs3776510, and rs429699 were selected to construct the haplotypes; no significant difference was found in a frequency of 5 haplotypes between the PD group and the control group. These results suggest that the SLC6A3 variant in rs40184 A allele may increase the risk of PD in northwest Han population and may be a biomarker of PD.